Shoottip culture and thirdcountry quarantine to facilitate the introduction of new Musa germplasm into West Africa - Vuylsteke, D.R.; Schoofs, J.; Swennen, Rony L.; Adejare, G.; Ayodele, M.; Langhe, E. de (1990)
Tissue culture is increasingly being used as a vehicle for the safe exchange of Musa germplasm. However, certain pathogens, e.g banana bunchy-top virus (BBTV), may pass undetected through in vitro culture. To meet the urgent need for introducing new desired germplasm for Musa breeding and reduced the risk of pathogen transfer, a germplasm-movement strategy based on two independent safeguards, viz. shoot-tip culture and third-country quarantine, was adopted. More than 270 Musa accessions have been introduced into Nigeria, including 33 with Black Sigoka resistance. BBTV has not been diagnosed in any of the introduced materials.